Efficacy of Commercial Insecticides against Tomato Leaf Miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in Palpa, Nepal - Anil Bastola; Subodh Raj Pandey; Anjali Khadka; Rajendra Regmi (Turkish Journal of Agriculture: Food Science and Technology)
A survey and field experiment were conducted to evaluate the efficacy of commercial insecticides against tomato leaf miner [Tuta absoluta (Meyrick)(Lepidoptera: Gelechiidae)] under farmer’s field condition in Palpa, Nepal from February 2018 to April 2018. It consists of seven treatments replicated three times. The treatments included: Abamectin 0.15% EC (dose: 0.3ml/liter), Imidachloprid 17.8% SL (dose: 0.3ml/liter), Spinosad 45% SC (0.3ml/liter), Azadirachtin 300 ppm (5ml/liter), Chlorantraniliprole 18.5% SC (0.3ml/liter), Emamectin benzoate 5% SC (2gm/liter) and control. Treatments were applied two times at 12 days interval. From the farmer survey, Tuta absoluta was identified as the major production problem of the study area. The field experiment revealed that there was a significant effect of insecticides in larval mortality and damage reduction. The lowest percentage of leaves damage was obtained in spinosad followed by chlorantraniliprole and emamectin benzoate and the lowest fruits damage was obtained in chlorantraniliprole followed by spinosad and emamectin benzoate. Similarly, the lowest larval population in both leaves and fruits was observed in chlorantraniliprole followed by spinosad and emamectin benzoate. Average mining in infested leaves and fruits was found non-significant at all days of observation. The rate of larval population reduction over control was found highest in chlorantraniliprole followed by spinosad and emamectin benzoate. Thus, chlorantraniliprole, spinosad and emamectin benzoate were superior insecticides for management of Tuta absoluta in the field condition.